Social trust and health seeking behaviours: A longitudinal study of a community-based active tuberculosis case finding program in the Philippines - Lincoln L.H. Lau; Natalee Hung; Warren Dodd; Krisha Lim; Jansel D. Ferma; Donald C. Cole (Elsevier, 2020)
Introduction: Social trust is an important driver of health seeking behaviours and plays a particularly important role for diseases that have a high degree of stigma associated with them, such as tuberculosis (TB). Individuals experiencing poverty also face additional social and financial barriers in accessing care for TB. We examined an active case finding (ACF) initiative embedded in a program targeting those living in poverty (Transform) implemented by International Care Ministries (ICM), a Philippine-based non-governmental organization (NGO), and analyzed how different forms of social trust may affect the initial uptake of ACF. Methods: Program monitoring data and a cross-sectional survey conducted at the beginning of Transform included six dimensions of social trust: satisfaction with family life, satisfaction with friendships, and level of trust in relatives, neighbours, pastor or religious leader, and local government officials. Amongst individuals suspected of having TB who received referrals post-screening, multilevel modelling examined the effects of social trust on rural health unit (RHU) attendance. Results: Among the subset of 3350 individuals who received TB screening in 51 communities, 889 (26.5%) were symptom positive and required referral to the RHU, but only 24.1% of those who received referrals successfully attended the RHU. Multilevel regression analysis showed that for each unit increase on the Likert scale in baseline level of family satisfaction and level of trust in relatives, the odds of attending an RHU was 1.03 times (95% CI: 0.99, 1.07) and 1.06 times greater (95% CI: 1.00, 1.11), respectively, independent of other factors. Conclusion: These results suggest that social trust in family members could play a valuable role in addressing stigma and rejection, both cited as barriers to higher screening rates. It is recommended that ACF programs that target TB, or other diseases that are stigmatized, prioritize trust-building as an important component of their intervention.